PERJANJIAN JUAL BELI E-COMERCE DITINJAU DARI HUKUM PERJANJIAN DAN UNDANG-UNDANG INFORMASI DAN TRANSASI ELEKTRONIK - Gunadi (Program Studi Hukum Keluarga Islam, 2024)
In a sale and purchase agreement over the internet, the transaction is not the same as a conventional sale and purchase agreement where the seller and buyer meet face to face. This raises the question of when an agreement occurs. To answer this, we can use the Acceptance Theory which teaches that an agreement occurs when the offering party directly receives an answer from the opposing party. The agreement between the seller and the buyer occurs when the seller receives an answer from the buyer. This can be done by several methods, namely through a single click,